PERAN UKURAN PERUSAHAAN DALAM MEMODERASI PENGARUH PROFITABILITAS DAN KEBIJAKAN UTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Sari, Revina Andika; Wahyuni, Ika; Widaninggar, Nanda (Fakultas Ekonomi dan Bisnis, 2024)
Pharmaceutical companies play a significant role in reforming the healthcare sector by researching, producing, developing, and distributing medications, including both generic and commercial drugs. This study aims to analyze and test the role of Company size in moderating the effects of Profitability and Debt policy on Firm value. The population for this study consists of 12 pharmaceutical companies listed on the Indonesia Stock Exchange from 2020 to 2022. The sampling technique used is purposive sampling. Data analysis and hypothesis testing in this study are conducted using Structural Equation Analysis - Partial Least Squares (PLS-SEM). The results of the hypothesis testing in the study show that Profitability has a negative but not significant effect on Firm value, while Debt policy has a significant negative effect on Firm value. Company size negatively moderates the effect of Profitability on Firm value, but this effect is not significant. Similarly, Company size negatively moderates the effect of Debt policy on Firm value, though this moderation is also not significant.